2013
DOI: 10.4161/cc.26061
|View full text |Cite
|
Sign up to set email alerts
|

Clamping down on mammalian meiosis

Abstract: T he RAD9A-RAD1-HUS1 (9-1-1) complex is a PCNA-like heterotrimeric clamp that binds damaged DNA to promote cell cycle checkpoint signaling and DNA repair. While various 9-1-1 functions in mammalian somatic cells have been established, mounting evidence from lower eukaryotes predicts critical roles in meiotic germ cells as well. This was investigated in 2 recent studies in which the 9-1-1 complex was disrupted specifically in the mouse male germline through conditional deletion of Rad9a or Hus1. Loss of these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 108 publications
(200 reference statements)
0
10
0
Order By: Relevance
“…In contrast with PCNA, the heterotrimeric nature of the eukaryotic 9-1-1 clamp adds complexity to its regulation and might expand its range of functions. In mammals and yeast, the functional diversification of the 9-1-1 clamp results from the appearance of Hus1 and Rad9 paralogs and isoforms (Lyndaker et al, 2013b). As an example, the formation of noncanonical complexes involving Rad9B, Rad1 and Hus1B has been suggested as an essential factor for proper completion of mammalian meiosis (Lyndaker et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast with PCNA, the heterotrimeric nature of the eukaryotic 9-1-1 clamp adds complexity to its regulation and might expand its range of functions. In mammals and yeast, the functional diversification of the 9-1-1 clamp results from the appearance of Hus1 and Rad9 paralogs and isoforms (Lyndaker et al, 2013b). As an example, the formation of noncanonical complexes involving Rad9B, Rad1 and Hus1B has been suggested as an essential factor for proper completion of mammalian meiosis (Lyndaker et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals and yeast, the functional diversification of the 9-1-1 clamp results from the appearance of Hus1 and Rad9 paralogs and isoforms (Lyndaker et al, 2013b). As an example, the formation of noncanonical complexes involving Rad9B, Rad1 and Hus1B has been suggested as an essential factor for proper completion of mammalian meiosis (Lyndaker et al, 2013b). It has also been reported that the human paralog Rad9B seems to be involved not only in the G1/S transition, but also in the response to nucleolar stress (Perez-Castro and Freire, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first group of genes were involved in the formation and repair of double-strand breaks during meiosis, which result in homologous recombination. This group included well-described genes such as BRCA2 , 41 EME1 , 42 GEN1 , 43 HSF1 , 44 MEI1 , 45 , 46 RAD51B , 47 RAD9B , a paralog of RAD9A , which is involved in DNA double-strand break repair during meiosis in mice, 48 MSH2 49 and PMS2 . 50 …”
Section: Resultsmentioning
confidence: 99%
“…The HUS1B (Checkpoint protein HUS1B) gene forms a complex with Rad9 and Rad1 which are involved in response to damaged DNA, triggering cell cycle checkpoint signaling and DNA repair mechanisms [ 44 ]. CACNA1D (Voltage-dependent L-type calcium channel subunit alpha-1D) is lowly expressed in RCC [ 45 ], and the expression level of CASP9 (Caspase-9) is altered in RCC by rs12124078 SNP [ 46 ], while CTSG (Cathepsin G) inhibition enhances apoptosis in human renal carcinoma (Caki) cells [ 47 ].…”
Section: Commonly Selected Genesmentioning
confidence: 99%